Legal Implications of Transfer of Land Rights Through Sale and Purchase Using a Replacement Certificate. Analysis of Legal Protection for the Original Owner. - Ramdhani, Iklil (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The issuance of replacement certificates often has legal implications for the transfer of land rights, especially if the application is based on false information. This can lead to legal flaws in the basis of the sale and purchase rights and result in the loss of the original owner's rights. In Decision Number 1440 K/Pdt/2023, the Supreme Court protected the interests of a good-faith buyer (Defendant X/Sunaryono), but failed to provide adequate protection for PT. BSD, the original owner, who suffered losses due to the unlawful actions of Ibung Muhamad's heirs (Defendant I-IX) who submitted illegal replacement certificates. The purpose of this study is to analyze the legal implications of the transfer of land rights through a sale and purchase using replacement certificates and to evaluate the legal protection for the original owner in the context of Supreme Court Decision Number 1440/K/PDT/2023. The research method used normative juridical methods with a case approach and a statute approach. Secondary data in the form of laws and regulations, court decisions, and legal literature were analyzed qualitatively. The research results obtained are that the legal implications of the transfer of land rights through a sale and purchase using a replacement certificate issued unlawfully have resulted in the loss of PT. BSD's rights, even though the company obtained the rights through a formal procedure in the form of a Deed of Transfer of Rights. Because the rights were not registered and there was no PPAT deed, its legal position was weaker compared to the second buyer (Defendant X) who was deemed to have good intentions by the Supreme Court in Decision Number 1440 K / Pdt / 2023. The decision shows that more protection is given to buyers who meet the formal requirements according to PP Number 24 of 1997 and Article 1320 of the Civil Code, but leaves an imbalance because it ignores the losses of parties who lose their rights due to the issuance of an unlawful replacement certificate. Therefore, legal protection for the original owner who is harmed remains important to enforce based on Article 1365 of the Civil Code, the Formulation of SEMA 7 of 2012, and Article 29 of the Supreme Court Law, by filing a civil lawsuit after obtaining a criminal decision stating that there has been an unlawful act. This step is an effort to balance legal certainty with the principle of substantive justice in the national land system.